Declarative programming and knowledge management : Conference on Declarative Programming, DECLARE 2017, unifying INAP, WFLP, and WLP, Würzburg, Germany, September 19-22, 2017, Revised selected papers /: Conference on Declarative Programming, DECLARE 2017, unifying INAP, WFLP, and WLP, Würzburg, Germany, September 19-22, 2017, Revised selected papers. (2018) - Unknown
No abstract available